Changes in pancreatic exocrine function in young at‐risk children followed to islet autoimmunity and type 1 diabetes in the ENDIA study. Issue 6 (9th June 2020) - Penno, Megan A.S.; Oakey, Helena; Augustine, Priya; Taranto, Mario; Barry, Simon C.; Colman, Peter G.; Craig, Maria E.; Davis, Elizabeth A.; Giles, Lynne C.; Harris, Mark; Haynes, Aveni; McGorm, Kelly; et al.
Abstract: Backgrounds: We aimed to monitor pancreatic exocrine function longitudinally in relation to the development of islet autoimmunity (IA) and type 1 diabetes (T1D) in at‐risk children with a first‐degree relative with T1D, who were followed prospectively in the Environmental Determinants of Islet Autoimmunity (ENDIA) study. Methods: Fecal elastase‐1 (FE‐1) concentration was measured longitudinally in 85 ENDIA children from median age 1.0 (IQR 0.7, 1.3) year. Twenty‐eight of 85 children (progressors) developed persistent islet autoantibodies at median age of 1.5 (IQR 1.1, 2.5) years, of whom 11 went on to develop clinical diabetes. The other 57 islet autoantibody‐negative children (non‐progressors) followed similarly were age and gender‐matched with the progressors. An adjusted linear mixed model compared FE‐1 concentrations in progressors and non‐progressors. Results: Baseline FE‐1 did not differ between progressors and non‐progressors, or by HLA DR type or proband status. FE‐1 decreased over time in progressors in comparison to non‐progressors (Wald statistic 5.46, P = .02); in some progressors the fall in FE‐1 preceded the onset of IA. Conclusions: Pancreatic exocrine function decreases in the majority of young at‐risk children who progress to IA and T1D.